Nilai-Nilai Pendidikan Akhlak dalam Surat Al-Hujurat Ayat 11-12 Telaah Tafsir Al-mishbah Karya Prof Dr. Quraish Shihab - Nurlaila; Gazali (Arus Jurnal Pendidikan, 2021)
Given the importance of Islamic education which includes morals, aqidah, and sharia, for the creation of harmonious environmental conditions, serious efforts are needed to instill these values and of course in accordance with the Qur'an and al-Hadith. Where one of these points is the morality of al-karimah which is a means to achieve success in the world and the hereafter, with morals also a person will be blessed by Allah SWT, loved by family and humans in general. Surah al-Hujurat verse 11-12 contains a very deep content (meaning) about moral education regarding the content of verses 11 to 12 which is a problem that often occurs and remains actual in society, it is necessary to research on the contents of the verse through a study of interpretation. Thus, this study aims to determine: (1) what moral values are contained in Surah Al-Hujurat verses 11-12. (2) Quraish Shihab's view of morality in Surah Al-Hujurat verses 11-12. (3) the relevance of moral values in Surah al-Hujurat verses 11-12 to Islamic education. This research includes library research, with a qualitative descriptive approach. In analyzing the data that has been collected, the researcher uses the tahliliy interpretation method or also known as the analytical method, namely an interpretive method that seeks to explain the meaning of the verses of the Qur'an with various aspects. The analysis refers to books and documents relevant to the research. The results of the study show that the values of moral education contained in the letter Al-Hujurat verses 11-12 are moral education that upholds the honor of fellow Muslims, moral education to avoid disgraceful traits such as making fun of, prejudice, and distancing from backbiting, then education to repent and be pious.